2003
DOI: 10.1191/1365782803li074oa
|View full text |Cite
|
Sign up to set email alerts
|

The effect of luminance uniformity on visibility level in road lighting

Abstract: This study evaluates the effect of low overall and longitudinal uniformities ratios on visual conditions as measured by visibility level at certain points of the road when the average visibility level on the road surface is adequate. A computer program has been developed to determine criteria for calculation of the road lighting based on visibility level to ensure driver comfort and safety. Five different arrangements, left hand single-sided, opposite, staggered, twin-bracket central and combined twin-bracket … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…For example, increased distance between poles reduces visibility of a target. 66 It is therefore expected that pavement obstacles present a range of contrasts, for which the empirical data used here 20 represent only one, and an extension of the relative visual performance model 67 might be a useful tool for exploring the implications.…”
Section: Resultsmentioning
confidence: 99%
“…For example, increased distance between poles reduces visibility of a target. 66 It is therefore expected that pavement obstacles present a range of contrasts, for which the empirical data used here 20 represent only one, and an extension of the relative visual performance model 67 might be a useful tool for exploring the implications.…”
Section: Resultsmentioning
confidence: 99%
“…Among these factors, average luminance and uniformity affect motorists' ability to detect potential hazards. The effect of various illuminances and uniformities on hazard detection has been extensively studied [37,38,39,40]. These studies report that motorists perform better at hazard detection when luminance and uniformity are increased.…”
Section: A Motorist's Perspectivementioning
confidence: 97%
“…The results also confirmed that the method can be used to distinguish the variation in the lighting conditions on different sections of the road (Figure 6). Hence, the method is a new tool for monitoring lighting performance and variations of visibility level along the road (see e.g., [35]). In addition, road lighting standards set requirements for maintained average luminance and its uniformity [33].…”
Section: Discussionmentioning
confidence: 99%